Surgical site infections - A threat to the health-care system: An observational study from a tertiary care hospital of Bihar - Kunal,; Kumar, Ashutosh; Kumar, Manish; Amaresh, Kumar; Ali Hassan, Ashif; Anupama, Anjoo (Asian Journal of Medical Sciences, 2023)
Background: A surgical site infection (SSI) is any infection occurring after a medical intervention. It is the most common nosocomial infection in low- and middle-income countries. It has raised both mortality and morbidity. Resistance to antibiotics due to irrational use has further added to the severity of the problem. Aims and Objectives: The current study was designed with the aim of determining the incidence of SSIs among patients operated on a tertiary care hospital, along with their antibiogram. Materials and Methods: An observational study with a cross-sectional design was conducted on 150 patients with suspected SSI were included in this study over a period of 1 year, from August 2021 to July 2022. An adult patient with pus, serous, or seropurulent discharge from the surgical wound was included in the study. Information was obtained using a pre-designed and pre-tested schedule. Identification of the colony was done by gram staining and inoculation on 5% sheep blood agar and Mac Conkey agar plates. Antimicrobial sensitivity testing was done. The data was analyzed using Microsoft Excel. Results: A total of 152 patients were included in the study. The incidence of SSI was found to be 38.2%. The mean age of the participants was 47.7 ± 21.6 years. The maximum incidence of SSI was noted in the 5th decade of life. Among the 58 patients’ samples, 65 aerobic bacterial colonies were isolated. Out of which Staphylococcus aureus and Escherichia coli were the commonest organisms. On performing an antibiogram, a higher degree of resistance was observed among Gram-negative organisms. Conclusion: SSI adds to the mortality as well as the morbidity of the patients. Not only this, but it also adds to the expenses. A more stringent surveillance system and reinforcement of the guidelines was the need of the hour to overcome this problem of hospital-acquired infections.